Orthostatic hypotension in Parkinson’s disease: effects on clinical features and disease severity-a systematic review and meta-analysis - Wang, Hui; Zhang, Chi; Xu, Dongxun (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is often associated with orthostatic hypotension (OH). However, research examining the relationship between OH and PD has yielded inconsistent results. This study conducts a meta-analysis to determine the associations between OH and clinical characteristics in individuals with PD.MethodsA systematic review and meta-analysis were performed by searching for studies related to PD and OH in the PubMed, Web of Science, Embase, and Cochrane databases. Data were pooled as necessary to calculate the odds ratios (OR) and weighted mean differences (WMD) with 95% confidence intervals (CI) for OH in PD patients. Heterogeneity was assessed using the I2 statistic. Meta-regression was conducted to detect the potential influences of disease duration on the differences in clinical features between PD patients with and without OH.ResultsA total of 26 articles involving 3,992 patients with Parkinson’s disease were included in our study. Patients with PD and OH were significantly older at the time of examination compared to those without OH (WMD 2.94 years, 95% CI 1.91–3.97 years; I2 = 64.1%). PD patients with OH had a significantly longer disease duration than those without OH (WMD 0.73, 95% CI 0.32–1.14). Furthermore, PD patients with OH exhibited significantly lower Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) scores than those without OH (WMD of − 0.99, 95% CI of −1.91 to −0.07; WMD of −1.86, 95% CI of −2.67 to −1.04). There were no significant differences in gender distribution, Hamilton Anxiety Rating Scale (HAMA) or Hamilton Depression Rating Scale (HAMD) scores among Parkinson’s disease patients with or without OH.ConclusionPatients with PD and OH tend to be older at the time of examination, exhibit a longer disease duration, and demonstrate more severe disease manifestations along with greater cognitive impairment compared to PD patients without OH.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251025263.